Enhancing compliance with privacy legislation through standardization - Michel Girard (Centre for International Governance Innovation (CIGI), 2023)
Data fuels the algorithms that run the products and systems people use every day, but without appropriate privacy regulations, data breaches can put users at risk. This paper proposes creating a privacy Regulatory Authority Advisory Body that would set privacy standards and ensure compliance among organizations. As digital transformation continues its rapid pace, compliance with privacy legislation is becoming increasingly important. For example, federal and provincial governments have proposed new privacy legislation called the Digital Charter Implementation Act, which will give users in Canada greater control over their personal information. As a result, privacy regulators will need to ensure that organizations that share data, either internally or with other parties, comply with this legislation.
Keywords: 330